An aberration-corrected STEM study of structural defects in epitaxial GaN thin films grown by ion beam assisted MBE. (June 2015) - Poppitz, David; Lotnyk, Andriy; Gerlach, Jürgen W.; Lenzner, Jörg; Grundmann, Marius; Rauschenbach, Bernd
Highlights: Direct growth of GaN thin films on 6H–SiC with high quality by ion beam assisted MBE (IBA-MBE). Detailed analysis of structural defects in GaN thin films by atomic-resolution Cs-corrected STEM. Comprehensive characterization of atomic structure at the GaN–SiC interface and of Amelinckx stacking mismatch boundary. Abstract: Ion-beam assisted molecular-beam epitaxy was used for direct growth of epitaxial GaN thin films on super-polished 6H–SiC(0001) substrates. The GaN films with different film thicknesses were studied using reflection high energy electron diffraction, X-ray diffraction, cathodoluminescence and primarily aberration-corrected scanning transmission electron microscopy techniques. Special attention was devoted to the microstructural characterization of GaN thin films and the GaN–SiC interface on the atomic scale. The results show a variety of defect types in the GaN thin films and at the GaN–SiC interface. A high crystalline quality of the produced hexagonal GaN thin films was demonstrated. The gained results are discussed.